An Ethnoarchaeological Study on Anthropic Markers from a Shell-midden in Tierra del Fuego (Southern Argentina): Lanashuaia II - Zurro Hernández, Débora (2017)
For many years the identification of activity areas has been carried out through the spatial distribution of lithics, zooarchaeological remains and specific features such as fireplaces. However, these data are rarely combined and integrated with results from specific analytical techniques such as phytoliths, organic matter, carbonates and multielemental analysis. This research presents the first results of an intrasite spatial analysis on a layer from the site Lanashuaia II, a shell-midden located on the Beagle Channel coast (Tierra del Fuego, Argentina). Ethnoarchaeology is used as a methodological tool to give content to the concept of anthropic markers by means of formulating archaeological hypothesis on the basis of ethnological information. This paper presents the application of specific anthropic markers, which have been designed and applied to identify ashy remains and waste areas through different combinations of proxies. The results show how an approach that integrates different techniques enhances data interpretation and allows to give visibility to activities that may not leave visible evidences.